Actualization of the problem of creation of special equipment for mobile stations of monitoring internet media and radio area based on the chassis of vehicles, which are theirtransport, energy and information-analytical base. - V. V. Savluchinskij; D. V. Blazhko (Системный анализ и прикладная информатика)
The specifics of the work of the combat crew for monitoring the Internet media and radio air in combat conditions determines the expected equipment of the combat duty vehicle of the crew for monitoring the Internet media and radio air.The combat duty vehicle refers to special equipment and is used in mobile monitoring stations for Internet media and radio broadcasting based on the chassis of vehicles, which are their transport, energy and information-analytical base.